2019
DOI: 10.3889/oamjms.2019.734
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Hip Fractures among Adult People in Babylon City, Iraq

Abstract: BACKGROUND: The fractures of hip joint considered as a serious problem in public health in the medical and socioeconomic issues, the incidence of the fracture neck femur is significantly increased with the increment of general population life span. AIM: The goal of this study is to highlight and focus on the most important risk factor for the hip fractures in our Babylon society, and to improve our understanding of the medical and social aspects of these predisposing factors. PATIENTS AND METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…This goes against other studies that considered smoking a greater risk factor for hip fracture [ 28 , 29 ]. However, our results were consistent with those of Al-Algawy et al in Iraq, who found that 61.3% of their cases were nonsmokers [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This goes against other studies that considered smoking a greater risk factor for hip fracture [ 28 , 29 ]. However, our results were consistent with those of Al-Algawy et al in Iraq, who found that 61.3% of their cases were nonsmokers [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study the mean age for the study sample was 74.32 (SD 10.8), making age a highly significant risk factor for fragility hip fractures. This accords with other studies evidencing increasing age as a major risk factor for non-pathological fragile fractures, such as Al-Algawy et al in 2019, who discovered that older people made up the majority of the group studied -age group of 70-79 [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is known that alcohol impairs judgment and stability, which can easily make an individual predispose self to road tra c accidents. Trauma and femur fracture in our study population are consistent with a study conducted in Babylon City, which notes that besides age and osteoporosis, other possible risk factors were cigarette smoking, lack of physical activity, medications that cause osteoporosis, disturbed mentation, consumption of excessive alcohol and caffeine, low body weight with tall stature, visual problems, generalized weakness, disability, or unsteady gait that increased risk for falls 35 .…”
Section: Discussionsupporting
confidence: 90%
“…age group and Alpantaki et al (2020) who confirmed that the incidence of hip fractures was higher in the "older" elderly than the "younger" one[16,17].…”
mentioning
confidence: 96%